NORMATIVE REGULATION IN THE FIELD OF FIRE SAFETY OF EXTERIOR WALLS ON THE OUTSIDE OF RESIDENTIAL AND PUBLIC BUILDINGS MADE OF WOODEN BUILDING STRUCTURES - Victor S. Gorshkov; Pavel S. Kopylov; Sergey T. Lezhnev; Ilya P. Eltyshev (Актуальные вопросы пожарной безопасности)
The article draws attention to the relevance of an objective review and improvement of regulatory system in the field of wooden housing due to the increased interest in wooden housing construction, in particular, the appearance of cross-laminated timber (CLT) panels. The advantages of such panels are a significant increase in the number of floors and the speed of construction of structures. This article is devoted to the analysis of existing regulatory requirements for ensuring fire safety of walls of exterior residential and public buildings made of wooden building structures and the development of a methodology for further experimental studies of such structural solutions. It is performed in order to update the regulatory framework: it is proposed to introduce an additional special classification by types of fire-resistant timber into the existing fire-technical classification in the Russian Federation.